Pomalidomide for the management of relapsed and refractory multiple myeloma: a case report and review of literature - S. V. Semochkin (Онкогематология)
Relapsed and refractory multiple myeloma (MM) is defined as progression during anticancer therapy, or within 60 days of therapy completion. Patients with double resistance to bortezomib and lenalidomide that is two key anti-myeloma drugs are considered to have a very poor prognosis, and new regimens are needed to improve this setting. Pomalidomide is an immunomodulatory drug third generation, studied in combination with low-dose dexamethasone (LDD) as salvage therapy for patients with double refractory. This article reviews the clinical pharmacology, therapeutic efficacy and safety, dosage and administration, peculiar properties of the practical application of pomalidomide. The article is illustrated by the description of a 59-year-old woman with relapsed and refractory MM, who received pomalidomide in combination with LDD. Medical history prior to treatment with pomalidomide was included 8 lines of therapy conducted over 6.5 years, with the formation of the double refractory to lenalidomide and bortezomib. In March 2012, treatment with pomalidomide (4 mg days 1–21 of a 28-day cycle) and LDD (160 mg / cycle) has been started as the ninth line. In total, up to March 2014 the patient received 30 cycles of therapy with pomalidomide. After the first 2 cycles documented partial response (52 % reduction of IgGk), the deepest response is received after 10 cycles (82 % reduction). The patient is alive at the time of this article. The duration of response to pomalidomide is 25 months and overall survival from the time of his appointment is more than 37 months. In addition, this review presents the results of base clinical trials testing pomalidomide and LDD. Problems of development of new treatment regimens based on pomalidomide for relapsed and refractory MM are also discussed.